PENANAMAN NILAI-NILAI KARAKTER MELALUI PENDIDIKAN; PENGAJARAN MATEMATIKA - Nurhikmah, Nurhikmah (Jurnal Cakrawala Ilmiah, 2025)
This study aims to instill Character values ​​Through Education; Mathematics Teaching. This type of research is library research. This study focuses on Instilling Character Values ​​through Education; Mathematics Teaching based on the implementation of mathematics teaching. data sources in this study, namely from other documents that support the writing. The source of documents selected for reference are articles, journals, and other documents related to the focus of the research. The research method that researchers use when conducting research is to search for journals, articles, and published articles that are relevant to the title and support the discussion. The data collection process for this study was carried out by searching on Google Scholar. The data analysis techniques used are content analysis and secondary data analysis.  This means using secondary sources to draw conclusions and obtain the data needed. The results of the study show that mathematics education; teaching has special characteristics or traits as an important science in value education, as a foundation for character education, namely (1) mathematics is structured deductively-axiomatically (2) inspired by agreements, (3) anti-Contradiction, (4) mathematics has many analogies, (5) mathematics can be alone and help other fields, (6) mathematics has abstract objects, and (7) mathematics has a universe of discourse. The universe of discourse shows that in the use of mathematics, clarity is needed in what scope the model or symbol is used. In our lives there is also a scope of discussion, a scope of study, so that misunderstandings do not occur, because there is often interference from a certain person in the area of ​​​​other people who are not in their environment. In addition, there are four important characters to be instilled through mathematics teaching, namely intelligent, caring, tough, and orderly/disciplined